2020
DOI: 10.3390/polym12061383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Esterification of Starch with a Mixture of Carboxylic Acids from Yarrowia lipolitica Fermentation Broth on Its Selected Properties

Abstract: Potato starch was esterified with carboxylic acids contained in the fermentation broth from Yarrowia lipolitica yeast production. Various acid concentrations and various roasting temperatures were used to determine effects of process conditions on ester properties, including the number of acid residues attached to starch chains, starch susceptibility to amylolysis, and thermal characteristics of starch phase transitions. Study results demonstrated the effect of both the composition and the dose of the fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Calibration curves (R 2 = 0.9990) were plotted in triplicates, using organic acid standards by Sigma-Aldrich (Poole, UK). The degree of substitution was expressed as the percentage content of acid residues in the preparations, according to Zdybel et al [19].…”
Section: Qualitative and Quantitative Analysis Of Organic Acids By Hplcmentioning
confidence: 99%
“…Calibration curves (R 2 = 0.9990) were plotted in triplicates, using organic acid standards by Sigma-Aldrich (Poole, UK). The degree of substitution was expressed as the percentage content of acid residues in the preparations, according to Zdybel et al [19].…”
Section: Qualitative and Quantitative Analysis Of Organic Acids By Hplcmentioning
confidence: 99%
“…Literature data published so far [ 37 , 43 , 45 , 46 , 88 ] corroborate a correlation between the amount of citric acid added, the degree of substitution, and resistant starch content in the modified preparation. However, in some research [ 45 , 46 , 62 , 81 ], this correlation occurred at citric acid doses lower than 30 g per 100 g of starch. The decreased RS at high citric acid concentrations is likely due to an excess of citric acid.…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 92%
“…In vitro digestibility tests of tapioca and maca starch esterified with citric acid indicated a slow digestion rate in term of the increase RS content [ 47 , 80 ]. Zdybel et al and Sorndech et al also reported a high resistance of potato or rice starch citrate to amylolysis [ 76 , 81 ]. Probably, the inhibited contact of digestive enzymes within the glucoside bonds of chemically modified starch appears due to the increased spatial hindrance resulting from the attachment of citric anhydride onto the starch molecule [ 63 ].…”
Section: Starch Citrates As Resistant Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also describe the effect of various additives on the physicochemical properties of starch, with particular emphasis put on the impact of these additives on the rheological properties of prepared pastes. However, our faculty has recently undertaken research in the area of so-called "green chemistry", in which the substrates naturally occurring in waste raw materials from the biotechnology industry were used for starch modification [12,13]. This work is part of the undertaken research direction.…”
Section: Introductionmentioning
confidence: 99%